Building a Community Legacy Together (BCLT) - An Intergenerational Program for Youth and Older Adults Aimed at Promoting a More Equitable Society - Barbara Baschiera; Karl Pillemer; Harry Yau (University of Bologna, 2019)
Societies in Europe and around the world are facing an unprecedented ageing of the population. This situation raises policy questions regarding how to ensure the inclusion of older adults so that they can enjoy full human rights in all domains of life. Ageism compromises human flourishing and represents a social justice issue. A solution is connecting the need for lifelong learning with intergenerational programs (IGPs), which promote inclusion, active citizenship and personal development. This concept is only partially understood, both at the policy and practice levels. To address this issue, an Italy - United States collaboration was formed to test an empowerment-based model, called "Building a Community Legacy Together" (BCLT), that creates environments for co-learning between older people and youth. Through this case study we argue that to support projects of living for older adults, it is necessary to rethink the current policy framework, offering opportunities for personal and social growth.